PENATAAN DAN PANDANGAN HUKUM ISLAM MUHAMMAD SHAHRUR - Asriyati, Asriyati (IAIN Samarinda, 2015)
Muhammad Shahrur is a contemporary scholar who offers a reformist approach to Islamic studies. In bringing forth his ideas especially those related to the Islamic issues, he takes into account sociological backgrounds surrounding them. His thoughts, therefore, are phenomenal and even controversial in some areas such as on the issues of polygamy, inheritance limit, veil, marriage, dowry, and á¹alÄq. This article analyzes Shahrurâ€™s thoughts related to these problems. It finds that Shahrurâ€™s ideas are based on the careful observation ofIslamic sciences coupled with theories in natural sciences. He thus argues that the nature of scientific truth is tentative and the Qurâ€™Än as a text is open to different meanings and interpretations.